2004
DOI: 10.1177/1470412904044797
|View full text |Cite
|
Sign up to set email alerts
|

It’s all about the Fit: The Hand, the Mobile Screenic Device and Tactile Vision

Abstract: This article takes notice of the particular relationship, or fit, between the hand and the mobile screenic device (MSD). Starting with biomechanics and industrial design, it describes the active and responsive quality of this relationship, which enables a manner of seeing that is material and dynamic -tactile. Informed by Benjamin's notion of the tactile, it explains tactile vision as sensual and diffuse and potentially charged with the immediacy and contingency of the everyday. Ultimately, this article assert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 9 publications
0
30
0
7
Order By: Relevance
“…This notion emphasizes the discussion of the convincibility of tactile vision (Cooley 2004), implying that learners can interact with images through tactility as well as vision. However, in mouse-mediated learning, the learner's cognition is distributed into the desktop screen and his/her hands operating a mouse; consequently, he/she cannot concentrate on the learning contents (Merrill 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This notion emphasizes the discussion of the convincibility of tactile vision (Cooley 2004), implying that learners can interact with images through tactility as well as vision. However, in mouse-mediated learning, the learner's cognition is distributed into the desktop screen and his/her hands operating a mouse; consequently, he/she cannot concentrate on the learning contents (Merrill 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Cooley (2004) introduced the concept of ''tactile vision,'' in which vision is activated by the hand and its engagement with the device, as a result of which seeing becomes tactile and is no longer limited to the eyes in the touchscreen interface. Tactile vision essentially implies seeing using the fingers or hands, and it involves interactions between the device, eyes, and hands.…”
Section: Introductionmentioning
confidence: 99%
“…In a person with visual impairment, the placement of the arms in the damaged visual hemifield 16 has been shown to improve the visual ability (Reed, Grubb and Steele 2006). Media scholar Heidi Rae Cooley (2004) has suggested that the relationship we form with handheld devices, such as the mobile phone, enables a form of tactile vision. She proposes the term "fit" for this relationship, which is based on the way we grasp the device and becomes familiar with it, to the extent that we enjoy playing with it or just holding it, keeping it in our hands even when it is not being used for its original purpose (phoning, taking pictures, etc.).…”
Section: Panoramic Perception and Tactile Visionmentioning
confidence: 99%
“…Recent work in new media studies has directed attention to the haptic dimensions of people's encounters with digital devices. The invention of devices that invite direct touch as part of their operation, such as smartphones and tablet computers, emphasises the embodied and sensory dimensions of these encounters (Cooley , Pink et al . ).…”
Section: Sensory Engagements With Datafied Bodiesmentioning
confidence: 99%